Review Artikel Beyond Use Date Sediaan Steril Rekonstitusi - wahyuni, LP eka; Warditiani, Ni Kadek; Suryani, N.P Febri; Sugiantara, I.W Eka; Rahayu, N.P Savitri; Dewi, N.P Apsari; Jayanti, N.K.P Aprilia; Adi P.S, I.K; Chantika P, N.K; Bayu J.K, I.M; Diah K, Shinta (Jurnal Farmasi Udayana; Vol. 13, No. 1, Tahun 2024, 2024)
Beyond Use Date (BUD) is the last date on which a medicinal preparation is considered stable and safe for use after reconstitution or preparation. Determination Beyond Use Date (BUD) functions to keep injection preparations sterile, protected from contaminants, protected from physical and chemical degradation. The method used in preparing this article is based on pharmaceutical literature, especially related literature steril coumponding method and pharmaceutical libraries. The purpose of this review article is to find out the importance of information regarding the BUD of reconstituted sterile preparations and how to use the drug after reconstitution. Determination of BUD for sterile preparations based on literature review United states of Phamacophea, American Society of Health-System Pharmacists (ASHP), and national and international published journals. The results of the article preparation are that the BUD determination is based on factors such as the chemical, physical and microbiological stability of the diluted drug. Reconstitution injection is a process in which a drug in dry form, such as powder or crystals, is converted into an injectable solution by adding a certain solvent or liquid. Quality requirements for reconstituted preparations include criteria that must be met by medicinal preparations after the reconstitution process to ensure their quality, safety and effectiveness. There are obstacles in determining the BUD for sterile preparations because the BUD time available is shorter after reconstitution, so there are several solutions that can be applied to maintain the stability of the preparation.